Wyłącz wspule czynnik przed nawias.
a)5x+10y=
b)4+5=
c)3a-3=
d)5xy-x=
e)-6a2-2a=
f)6a2-12ab=
g)1:2xy-1:2x=
h)1:3a2b+1:9ab2=
i)2xyz-4x2y2z+xyz2=
j)stv2-stv+tv2=
2-kwadrat
np-1:3-jedna druga
Przedastaw w postaci iloczynu.
d)10a2-2ab=
e)xy-x2y=
f)6a-24b+30c=
g)12ab2+16b2=
h)x3-2xkwadrat+x=
i)2xy+3x-x2y=
3-szescian

2

Odpowiedzi

Najlepsza Odpowiedź!
2010-02-25T17:24:07+01:00
A)5x+10y=5(x+2y)
b)4+5=
c)3a-3= 3(a-1)
d)5xy-x= x*(5y-1)
e)-6a2-2a=a²*(-6-1)
f)6a2-12ab=6a*(a-2b)
g)1:2xy-1:2x=½ x*( y-1)
h)1:3a2b+1:9ab2= ⅓ ab*(a+⅓b)
i)2xyz-4x2y2z+xyz2=xyz*(2-4xy+z)
j)stv2-stv+tv2=tv *(sv- s+v)

Przedastaw w postaci iloczynu.
d)10a2-2ab=2a *( 5a - b)
e)xy-x2y= xy *(1- x)
f)6a-24b+30c= 6 *(a-4 b+5c)
g)12ab2+16b2=4b*(3ab+4b)
h)x3-2xkwadrat+x=x *(x²- 2x+1)
i)2xy+3x-x2y= x * ( 2y+ 3- xy)
2010-02-25T17:43:15+01:00
A) 5(x+2y)
b) 4+5=9
c) 3(a-1)
d) x(5y-1)
e) -2a(3a+1)
f) 6a(a-2b)
g) 1:2x(y-1)
h) 1:3ab(a+1:3b)
i) 2xyz(1-2xy+z)
j) tv(vs-s+v)

d) 2a(5a-b)
e) xy(1-x)
f) 6(a-4b+5c)
g) 4b2(3a=4)
h) x(X2-2x2+1)
i) x(2y+3-xy)